(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to one of the questions of Ukrainian life after the liquidation of Cossackhood – river navigation. The author demonstrates that traffic safety organization in Dnieper waterway in the last quarter of the XVIII century was a minor question solved together with the primary one – increasing the Dnieper freight flow.